Facilitating Racial Equity: Evaluating a Leadership Workshop Series for School Social Workers - Summer G Woodside; Veronica Hardy (International Journal of School Social Work, 2020)
This article provides an overview of a leadership training workshop series designed to provide professional development to Pre-K through 12th grade school social workers about racial equity and leadership. The series' objectives included promoting social workers’ understanding of and obligation to facilitating racial equity in schools, analyzing educational data through a racial equity lens, conceptualizing school social workers as influencers in addressing racial inequities in schools, and collaborating with school professionals of various disciplines to practice and implement evidence-based approaches for facilitating racial equity in schools. The authors conducted five workshops that were developed based on state school social work practice standards, school systems data, scholarly literature, and social work values and ethics, and used a pretest/ posttest, workshop surveys, and a follow-up survey one year later to measure change in participants’ knowledge, self-readiness in assessing, facilitating, and leading change in school settings, and self-perceptions as leaders versus support staff. Survey findings are discussed in relation to participants’ perceived identity in the school environment, knowledge of racial equity, perceived readiness in assessing and facilitating racial equity in school cultures, perceived identity in the school environment, and possible barriers to promoting a racially equitable school culture.
Keywords: racial equity; school social work; values and ethics; leadership; school culture